CASE REPORTS:Aortic thrombosis as a complication of intraaortic balloon - Kaminski, Karol; Knapp, Małgorzata; Werel, Dorota; Musial, Wlodzimierz (Archives of Medical Science, 2009)
Intra-aortic balloon counterpulsation is often used in critically ill patients with cardiac disease. Commonly accepted indications for its use include cardiogenic shock and mechanical complications of acute myocardial infarction (e.g. ventricular septal defect). The potential benefits of counterpulsation must be weighed against its possible severe thrombotic and hemorrhagic complications. Here we describe a 72-year old female with interventricular septum rupture complicating the course of acute myocardial infarction, in whom the intra-aortic balloon was used to stabilize the circulation prior to the surgery. Despite anticoagulation she developed a thrombus in the abdominal aorta. The risk – benefit ratio and possible ways to predict the complications are discussed.